Silicon-carbon composite material, preparation method thereof and lithium ion battery
Patent Information
- Application Number
- CN202611076922.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-07-15
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-20
AI Technical Summary
甲硅烷气体易燃,且有毒,其大规模生产使用给企业带来较大的安全隐患
本发明采用微米硅为硅源,三聚氰胺为碳源,氯化铜为助剂,通过将微米硅、三聚氰胺和氯化铜混合后进行热处理,使得氯化铜高温分解产生氯气,氯气与微米硅反应生成四氯化硅气体,同时三聚氰胺高温分解产生氢气并形成多孔碳,四氯化硅气体被氢气还原为纳米硅颗粒并原位附着于三聚氰胺衍生的多孔碳上,得到了硅碳复合材料。即本发明通过原位反应的方法,可将微米硅颗粒碎化,尺寸减小至30~100 nm,并与多孔碳材料复合形成硅碳复合材料。上述制备方法无需使用易燃有毒的甲硅烷气体,制备过程安全,适合大规模生产;同时,得益于硅的纳米尺寸(30~100nm),该硅碳复合材料作为锂离子电池负极材料能够有效缓释硅在充放电过程中的体积膨胀效应,显示出良好的循环稳定性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery anode material preparation, and particularly to a method for preparing a silicon-carbon composite material, the prepared composite material of which can be used as a lithium-ion battery anode material. Background Technology
[0002] Compared to other rechargeable batteries, lithium-ion batteries boast high energy density and long cycle life, and are already widely used in household appliances. When used as a power source for automobiles, even higher energy density is required. However, graphite anodes have a theoretical specific capacity of only 372 mAh / g, which is insufficient to meet the high energy density demands of automobiles. Silicon, with a specific capacity as high as 4200 mAh / g, has led to the widespread adoption of silicon-carbon composite materials to overcome its significant volume expansion (300%).
[0003] Most commercially available silicon-carbon composite materials currently on the market are prepared using silane gas as the silicon source and porous carbon as the carrier via vapor deposition. Silane gas is flammable and toxic, and its large-scale production and use pose significant safety hazards to enterprises. Summary of the Invention
[0004] To address the problems associated with using silane gas as the silicon source in the preparation of the aforementioned silicon-carbon composite materials, this invention provides a silicon-carbon composite material, its preparation method, and a lithium-ion battery. This method uses micron-sized silicon as a raw material, and the composite material with carbon exhibits excellent electrochemical performance. Compared with silane gas, it does not pose any safety risks during large-scale production.
[0005] Compared with the prior art, the present invention has the following beneficial effects: This invention uses micron-sized silicon as the silicon source, melamine as the carbon source, and copper chloride as an additive. The mixture of micron-sized silicon, melamine, and copper chloride is heat-treated, causing the copper chloride to decompose at high temperature to produce chlorine gas. The chlorine gas reacts with the micron-sized silicon to generate silicon tetrachloride gas, while the melamine decomposes at high temperature to produce hydrogen gas and form porous carbon. The silicon tetrachloride gas is reduced by the hydrogen gas to nano-silicon particles, which then attach in situ to the melamine-derived porous carbon, resulting in a silicon-carbon composite material. In other words, this invention uses an in-situ reaction method to break down micron-sized silicon particles to a size of 30-100 nm, and then combines them with porous carbon materials to form a silicon-carbon composite material. The above preparation method does not require the use of flammable and toxic silane gas, making the preparation process safe and suitable for large-scale production. Furthermore, thanks to the nanoscale size of silicon (30-100 nm), this silicon-carbon composite material, as a negative electrode material for lithium-ion batteries, can effectively mitigate the volume expansion effect of silicon during charge and discharge, exhibiting good cycle stability.
[0006] The in-situ reaction mechanism by which micron-sized silicon particles break down into nano-sized silicon is as follows: (1) High-temperature decomposition of copper chloride: CuCl2--- Cu +Cl2↑ (2) At high temperature: Si + Cl2 → SiCl4↑ (3) High-temperature melamine decomposes to produce hydrogen gas, forming porous carbon; (4) SiCl4↑+H2--- Si + HCl↑, to obtain nano-silicon particles.
[0007] Furthermore, by controlling the mass ratio of micron-sized silicon to melamine to 1:(1~30), the present invention can regulate the amount of porous carbon generated and its pore structure, providing sufficient loading space and supporting framework for nano-silicon particles, which is beneficial to further slow down the volume expansion of silicon.
[0008] Furthermore, by controlling the mass ratio of micron-sized silicon to copper chloride to be 1:(1~5), the present invention can regulate the amount of chlorine generated, thereby effectively controlling the degree of conversion of micron-sized silicon to nano-sized silicon and the final size of silicon particles.
[0009] Furthermore, by controlling the heat treatment temperature to 700~900℃ and the time to 0.5~2h, the present invention can ensure that copper chloride is fully decomposed, melamine is fully carbonized, and the chlorination and reduction reactions of silicon are fully carried out.
[0010] Furthermore, the present invention uses hydrochloric acid for pickling, which can effectively remove Sn metal impurities generated in the product.
[0011] Furthermore, the present invention uses methanol to soak the solid obtained after solid-liquid separation, which can dissolve excess melamine byproducts and improve the purity of the product.
[0012] Furthermore, the present invention uses argon or nitrogen as an inert atmosphere, which can provide a stable inert environment for the heat treatment process and prevent the occurrence of side reactions.
[0013] In the silicon-carbon composite material prepared by this invention, the silicon particles have a size of 30~100 nm. Due to their small size, even if the volume expands by 300%, they can still exhibit good electrochemical performance within a limited space supported by carbon materials. Attached Figure Description
[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0015] Figure 1 This is the X-ray diffraction pattern of the product of Example 1 of the present invention.
[0016] Figure 2 This is a transmission electron microscope image of the product of Example 2 of the present invention.
[0017] Figure 3 This is a charge-discharge curve of the product of Example 3 of the present invention as a negative electrode material for a lithium-ion battery.
[0018] Figure 4 This is a cycle stability diagram of the product of Example 4 of the present invention as a negative electrode material for lithium-ion batteries. Detailed Implementation
[0019] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.
[0020] It should be noted that the process equipment or apparatus not specifically mentioned in the following embodiments are all conventional equipment or apparatus in the art.
[0021] It should be noted that the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products, or apparatuses. Furthermore, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not intended to limit the order of the method steps or define the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.
[0022] Most existing commercial silicon-carbon composite materials are prepared using vapor deposition with silane gas as the silicon source. Silane gas is flammable and toxic, posing significant safety hazards to enterprises during large-scale production. To address these safety concerns, this invention utilizes micron-sized silicon as the silicon source, melamine as the carbon source, and copper chloride as an additive. The process involves reacting chlorine gas generated from the high-temperature decomposition of copper chloride with the micron-sized silicon to generate silicon tetrachloride gas, which is then reduced to nano-silicon particles by hydrogen gas generated from the decomposition of melamine. Simultaneously, porous carbon derived from melamine serves as a carrier to in-situ support the nano-silicon particles. This avoids the use of flammable and toxic silane gas, achieving a safe and large-scale preparation method for silicon-carbon composite materials. The resulting product exhibits excellent cycle stability as a negative electrode material for lithium-ion batteries.
[0023] The method for preparing the silicon-carbon composite material of the present invention includes the following steps: (1) Micron-sized silicon, melamine, and copper chloride are ground and mixed to obtain a mixture; (2) The mixture is heat-treated under an inert atmosphere to obtain a heat-treated product; the heat-treated product is acid-washed and separated into solid and liquid components to obtain a silicon-carbon composite material.
[0024] In this invention, micron-sized silicon is used as the silicon source. Copper chloride acts as an auxiliary agent (i.e., a chlorinating agent) during heat treatment, decomposing at high temperature to generate chlorine gas. The chlorine gas reacts with the micron-sized silicon to generate silicon tetrachloride gas. Melamine acts as the carbon source during heat treatment, decomposing at high temperature to generate hydrogen gas and form porous carbon. The formed porous carbon serves as a carrier for loading the in-situ generated nano-silicon particles. The hydrogen gas generated from the decomposition of melamine acts as a reducing agent to reduce the silicon tetrachloride gas to nano-silicon.
[0025] During heat treatment, the following in-situ reaction occurs: (1) High-temperature decomposition of copper chloride: CuCl2--- Cu +Cl2↑ (2) At high temperature: Si + Cl2 → SiCl4↑ (3) High-temperature melamine decomposes to produce hydrogen gas, forming porous carbon; (4) SiCl4↑+H2--- Si + HCl↑, to obtain nano-silicon particles.
[0026] To further optimize the structure and properties of the product, this invention optimizes the mass ratio of micron-sized silicon to melamine. The mass ratio of micron-sized silicon to melamine can be 1:1, 1:10, 1:20, or 1:30, or any ratio within the range of 1:(1~30). By adjusting this ratio, the amount of porous carbon generated and its pore structure can be controlled, providing sufficient loading space and supporting framework for the nano-silicon particles.
[0027] To further optimize the structure and properties of the product, this invention optimizes the mass ratio of micron-sized silicon to copper chloride. The mass ratio of micron-sized silicon to copper chloride can be 1:1, 1:2, 1:4, or 1:5, or any ratio within the range of 1:(1~5). By adjusting this ratio, the amount of chlorine generated can be controlled, thereby controlling the degree of conversion of micron-sized silicon to nano-sized silicon and the final size of the silicon particles.
[0028] To ensure the complete progress of each reaction, the present invention optimizes the temperature and time of the heat treatment. The heat treatment temperature can be 700°C, 800°C, or 900°C, or any temperature within the range of 700-900°C. The heat treatment time can be 0.5h, 1h, or 2h, or any time within the range of 0.5-2h. Under these temperature conditions, copper chloride can be fully decomposed, melamine can be fully carbonized and decomposed to produce hydrogen gas, and the chlorination reaction of silicon and the reduction reaction of silicon tetrachloride can proceed fully. The heat treatment can be carried out in conventional heat treatment equipment in the art, such as a tube furnace.
[0029] To effectively remove metallic impurities (such as copper) and unreacted raw materials from the product, this invention preferably uses hydrochloric acid for pickling. The concentration of hydrochloric acid can be a conventional pickling concentration in the art, and those skilled in the art can select it according to actual needs. The solid-liquid separation step after pickling can use conventional solid-liquid separation methods in the art, such as vacuum filtration, centrifugation, etc., to separate the pickled solid product from the liquid.
[0030] To further remove residual impurities from the product and improve its purity, this invention includes a step of soaking the obtained solid in methanol after solid-liquid separation. The methanol soaking time can be 10 hours, or it can be adjusted according to actual needs.
[0031] To provide a stable inert environment and prevent side reactions, the present invention preferably uses argon or nitrogen as the inert atmosphere.
[0032] In the silicon-carbon composite material prepared by the above method, the size of the silicon particles is 30~100nm. Specifically, when the particle size of micron-sized silicon is 1 micron, the size of the obtained silicon particles is approximately 30nm; when the particle size of micron-sized silicon is 3 microns, the size of the obtained silicon particles is approximately 50nm; when the particle size of micron-sized silicon is 5 microns, the size of the obtained silicon particles is approximately 70nm; and when the particle size of micron-sized silicon is 10 microns, the size of the obtained silicon particles is approximately 100nm.
[0033] Example 1 Three solid powders with a particle size of 1 micrometer—silicon, melamine, and copper chloride—were ground and mixed evenly, with the mass ratio of micron-sized silicon to melamine being 1:1 and the mass ratio of micron-sized silicon to copper chloride being 1:1.
[0034] The mixture was kept at 800°C for 1 hour under an argon atmosphere. After cooling, the product was washed with hydrochloric acid, then filtered and dried. The dried product was soaked in methanol for 10 hours, filtered, and dried again to obtain a silicon-carbon composite material. The silicon particle size was 30 nm.
[0035] Example 2 Three solid powders with a particle size of 3 micrometers—silicon, melamine, and copper chloride—were ground and mixed evenly, with the mass ratio of micron-sized silicon to melamine being 1:10 and the mass ratio of micron-sized silicon to copper chloride being 1:2.
[0036] The mixture was kept at 800°C for 1 hour under a nitrogen atmosphere. After cooling, the product was washed with hydrochloric acid, then filtered and dried. The dried product was soaked in methanol for 10 hours, filtered, and dried again to obtain a silicon-carbon composite material. The silicon particle size was 50 nm.
[0037] Example 3 Three solid powders with a particle size of 5 micrometers—silicon, melamine, and copper chloride—were ground and mixed evenly, with the mass ratio of micron-sized silicon to melamine being 1:20 and the mass ratio of micron-sized silicon to copper chloride being 1:4.
[0038] The mixture was kept at 800°C for 1 hour under an argon atmosphere. After cooling, the product was washed with hydrochloric acid, then filtered and dried. The dried product was soaked in methanol for 10 hours, filtered, and dried again to obtain a silicon-carbon composite material. The silicon particle size was 70 nm.
[0039] Example 4 Three solid powders with a particle size of 10 micrometers—silicon, melamine, and copper chloride—were ground and mixed evenly, with the mass ratio of micron-sized silicon to melamine being 1:30 and the mass ratio of micron-sized silicon to copper chloride being 1:5.
[0040] The mixture was kept at 800°C for 1 hour under a nitrogen atmosphere. After cooling, the product was washed with hydrochloric acid, then filtered and dried. The dried product was soaked in methanol for 10 hours, filtered, and dried again to obtain a silicon-carbon composite material. The silicon particle size was 100 nm.
[0041] Figure 1 This is the X-ray diffraction pattern of the silicon-carbon composite material produced in Example 1 of this invention. After Gaussian fitting, it can be seen that the 24° peak belongs to the (002) characteristic diffraction peak of carbon and the 31° peak belongs to the diffraction peak of amorphous silicon, proving that the obtained nano-silicon is an amorphous material.
[0042] Figure 2 This is a scanning electron microscope (SEM) image of the silicon-carbon composite material produced in Example 2 of this invention. From... Figure 2 It can be seen that the particles within the porous carbon are nano-silicon particles, with a size of approximately 50 nm. This result demonstrates that the preparation method of this invention can break down micron-sized silicon into nano-silicon, forming a silicon-carbon composite material.
[0043] Figure 3This is a charge-discharge curve of the product of Example 3 of the present invention as a negative electrode material for lithium-ion batteries. The discharge curve shows the characteristic discharge plateau of silicon, and the specific capacity of the silicon-carbon composite material is as high as about 1800 mAh / g.
[0044] Figure 4 The graph shows the cycle stability of the product of Example 4 of this invention as a negative electrode material for lithium-ion batteries. It can be seen that after 200 cycles, the capacity retention rate is higher than 95% compared with the discharge capacity of the second cycle, indicating that the silicon-carbon composite material prepared by this invention has good cycle stability.
[0045] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of this invention.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that, Includes the following steps: (1) Grind and mix three solid powders, namely micron-sized silicon, melamine and copper chloride, evenly to obtain a mixture; (2) The mixture was heat-treated under an inert atmosphere. After the product was cooled, it was acid-washed and separated into solid and liquid components to obtain a silicon-carbon composite material.
2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that, The mass ratio of micron-sized silicon to melamine is 1:(1~30).
3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that, The mass ratio of micron-sized silicon to copper chloride is 1:(1~5).
4. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that, Micron-sized silicon has dimensions ranging from 1 to 10 micrometers.
5. The method for preparing silicon-carbon composite material according to claim 1, characterized in that, The heat treatment temperature is 700~900 ℃, and the time is 0.5~2 h.
6. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that, The pickling solution used is hydrochloric acid.
7. The method for preparing silicon-carbon composite material according to claim 1, characterized in that, After solid-liquid separation, the obtained solid was soaked in methanol. After soaking, the obtained solid was dried to obtain a silicon-carbon composite material.
8. The method for preparing silicon-carbon composite material according to claim 1, characterized in that, The inert atmosphere is either argon or nitrogen.
9. A silicon-carbon composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that, The silicon particle size in silicon-carbon composites is 30~100 nm.
10. A lithium-ion battery, characterized in that, The silicon-carbon composite material described in claim 9 is used as the negative electrode material.